Graciliano Ramos e Santa Rosa: palavra e imagem em perspectiva - Borges, Francieli Daiane (2021)
(1938), written by Graciliano Ramos (1892-1956), and the covers made by Tomás Santa Rosa (1909-1953) for these books. Among the suggestions of reading made in this work, we reflect about the relationship between the graphical apparatus presented in the books having its role in the construction of their meaning by the readers. We also dedicate ourselves, in the three chapters composing this work, to verify the relationship of these two artists regarding the sociability instituted in the publishing market in the first half of the twentieth century in Brazil. This is done mainly through the assessment of contemporary documents. We also highlight the pertinence of the concepts and theories elaborated by Gérard Genette regarding the relationship between the reading of literary works and the artwork in their covers. Thanks to the indications made by Santa Rosa, in his Roteiro de Arte (1952), as well as by the literary criticism in newspapers found in the Hemeroteca Digital da Biblioteca Nacional, we were able to circumscribe the conditions in which both intellectuals worked and, specially, to study the manifold place of covert art in the construction of the meanings the novels assumed.